Strategi Pengelolaan Usaha Kelompok Usaha Bersama (KUBE) - Misfi Laili Rohmi (Jurnal Nusantara Berbakti, 2023)
The Joint Business Group (KUBE) is one of the government's efforts to alleviate poverty by providing assistance to KUBE members to develop businesses in groups. The purpose of this service is to provide KUBE members with an understanding of business management so that KUBE can progress and prosper its members. The implementation method is carried out through coordination with village officials to determine the location and time of service. Furthermore, community service activities were carried out at KUBE Lestari Pekon Gumuk Rejo, Pagelaran District, Pringsewu, Lampung by delivering material directly/lectures and practice. The result of this activity is that participants gain knowledge regarding budget control and also marketing by utilizing market places and social media. Participants can also make simple bookkeeping as a basis for business financial reports.